2022
DOI: 10.3389/fphar.2022.1031509
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV improves the pharmacokinetics of febuxostat in rats with hyperuricemic nephropathy by regulating urea metabolism in gut microbiota

Abstract: Hyperuricemic nephropathy (HN) is a common clinical complication of hyperuricemia. The pathogenesis of HN is directly related to urea metabolism in the gut microbiota. Febuxostat, a potent xanthine oxidase inhibitor, is the first-line drug used for the treatment of hyperuricemia. However, there have been few studies on the pharmacokinetics of febuxostat in HN animal models or in patients. In this study, a high-purine diet-induced HN rat model was established. The pharmacokinetics of febuxostat in HN rats was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, AS-IV decreased the protein levels of TNF-α and IL-6 in adipocytes through the miR-21/PTEN/PI3K/AKT signaling pathway [67]. Other studies have shown that AS-IV can interact with the gut microbiota and be decomposed and used by the gut microbiota, inducing the production of various beneficial short-chain fatty acids, which can reduce the degree of systemic inflammation [39,68].…”
Section: Discussionmentioning
confidence: 99%
“…However, AS-IV decreased the protein levels of TNF-α and IL-6 in adipocytes through the miR-21/PTEN/PI3K/AKT signaling pathway [67]. Other studies have shown that AS-IV can interact with the gut microbiota and be decomposed and used by the gut microbiota, inducing the production of various beneficial short-chain fatty acids, which can reduce the degree of systemic inflammation [39,68].…”
Section: Discussionmentioning
confidence: 99%
“…Parabacteroides is also a urease-related genus, and its elevation is involved in hyperuricemia-related renal injury (Zhao et al, 2022). Zhao et al (2022) reported that the abundance of Parabacteroides increases in rats with hyperuricemic nephropathy. In addition, Corynebacterium is a group of Gram-positive bacteria and is frequently categorized as opportunistic pathogens (Luo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…P. johnsonii is implicated in the regulation of host immunity (Cui et al, 2022). Parabacteroides is also a urease‐related genus, and its elevation is involved in hyperuricemia‐related renal injury (Zhao et al, 2022). Zhao et al (2022) reported that the abundance of Parabacteroides increases in rats with hyperuricemic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The renal organ assumes a crucial function in the processes of drug metabolism and elimination, rendering its susceptibility to the adverse effects of drug-induced toxicity ( Bajaj et al, 2018 ). The LC-MS/MS study conducted by Zhao et al (2022) demonstrated that febuxostat, a drug used to treat hyperuricemia, exhibited renal accumulation in rats with significant renal impairment following repeated administrations. Their findings revealed a plausible detrimental impact on individuals with pre-existing renal impairment.…”
Section: Introductionmentioning
confidence: 99%